Confirmation of highly pathogenic avian influenza H5N1 in skuas, Antarctica 2024 - Bennett-Laso, Benjamín; Berazay, Bárbara; Muñoz, Gabriela; Ariyama, Naomi; Enciso, Nikita; Braun, Christina; Krüger, Lucas; Barták, Miloš; González-Aravena, Marcelo; Neira, Victor (Frontiers in Veterinary Science, 2024)
From December 2023 to March 2024, a surveillance program aiming to detect Highly Pathogenic Avian Influenza (HPAI) H5N1 was conducted on Antarctica territories, specifically at Fildes Peninsula (King George Island, Maritime Antarctic), and James Ross Island. At Fildes Peninsula, samples from marine birds and mammals were collected from four accessible sampling locations with significant animal colonies: Ardley Island, hosting a large concentration of Gentoo penguins (Pygoscelis papua); Ardley Cove, where small groups of likely non-breeding Chinstrap penguins (Pygoscelis antarcticus) were present; seal haul-out sites of Southern elephant (Mirounga leonina) and Weddell (Leptonycotes wedellii); and, a nesting site of Southern giant petrels (Macronectes giganteus). Additionally, six samples were collected from five dead skuas near the Lachman lakes on James Ross Island (63.7989S, 57.8105W) on March 3, 2024. Despite collecting a total of 943 samples from Fildes Peninsula, all results tested negative for HPAI, and no animals displayed clinical signs or behaviors consistent with HPAI infection. However, all skua samples from James Ross Island tested positive for HPAI H5N1 clade 2.3.4.4 by specific real-time RT-PCR reactions, confirming the first recorded HPAI-related mortality event in Antarctica (south of 60°S), specifically in skuas. Further research is necessary to genetically characterize the virus and better understand the role of skuas in viral dissemination in Antarctica.